Mother Earth Tuya's Marriage. Issue 2 (1st September 2008) - Chen, Ya-chen
Following Wang Quanan's claims about the topics of his film, I argue that the interrelationship he describes constitutes a sort of ecofeminist intertextuality that challenges stereotypical patriarchal marital systems and gender ideologies. Essentially speaking, Tuya is Mother Earth; her illness, a consequence of the overuse of her physical powers, mirrors the abuse of the natural environment. The audiovisual ecofeminism in the cinematic story of Mother Earth Tuya's marriage revises the stereotypical patriarchal definitions of polygamy, division of labor, women working force, dowry, divorce, men's ownership of women, and even penis envy or castration fear.